Practice of Hospital Pharmacy in Bangladesh: Current Perspective - Paul, Tripti Rani; Rahman, Md Ajijur; Biswas, Mohitosh; Rashid, Mamunur; Islam, Md Anwar Ul (Bangladesh Pharmaceutical Journal, 2015)
Although hospital pharmacists are recognized for its importance as health care provider in many developed countries, in most developing countries it is still underutilized. The aim of the present study was to summarize the current scenario of pharmacy practices in four hospitals of Bangladesh and to identify the pharmacists rolesin these seftap. The study was conducted through convenient sampling method using a well-designed 14-item questionnaire to collect the opinions from the respondents. The results showed that hospital pharmacy service, as a unique department of hospital, existed in 50% of the studied hospitals where activities were done by graduate pharmacists and they were also involved in different departments to provide clinical services to the patients. The rest 50% of the studied hospitals had no hospital pharmacy service. Only a retail drug store inside the hospital was present and there was no diploma or graduate or any pharmacy technician for providing patient care. This study concludes that hospital pharmacy practice is just started in some private modern hospitals in Bangladesh which is inaccessible for the majority of peoples due to high patients cost of these hospitals. DOI: http://dx.doi.org/10.3329/bpj.v17i2.22339 Bangladesh Pharmaceutical Journal 17(2): 187-192, 2014